Robert Recorde Tudor Polymath, Expositor and Practitioner of Computation - Williams, Jack (Springer eBooks.)
The 16th-Century intellectual Robert Recorde is chiefly remembered for introducing the equals sign into algebra, yet the greater significance and broader scope of his work is often overlooked. Robert Recorde: Tudor Polymath, Expositor and Practitioner of Computation presents an authoritative and in-depth analysis of the man, his achievements and his historical importance. This scholarly yet accessible work examines the latest evidence on all aspects of Recorde?s life, throwing new light on a character deserving of greater recognition. Topics and features: Presents a concise chronology of Recorde's life Examines his published works; The Grounde of Artes, The Pathway to Knowledge, The Castle of Knowledge, and The Whetstone of Witte Describes Recorde?s professional activities in the minting of money and the mining of silver, as well as his dispute with William Herbert, Earl of Pembroke Investigates Recorde?s work as a physician, his linguistic and antiquarian interests, and his religious beliefs Discusses the influence of Recorde's publisher, Reyner Wolfe, in his life Reviews his legacy to 17th-Century science, and to modern computer science and mathematics This fascinating insight into a much under-appreciated figure is a must-read for researchers interested in the history of computer science and mathematics, and for scholars of renaissance studies, as well as for the general reader.